(untitled) (FULafia Journal of Science and Technology, 2021)
This research work investigated the faults analysis usually encountered on a 33kv distribution system using the Abeokuta business hub in Ogun state, Nigeria as a case study. The available data which was analyzed statistically revealed that the bad condition of the physical structure of the 33kv distribution network was the major cause of frequent outage in Abeokuta and its environs. Accordingly, the deplorable state of the physical structure triggers most technical faults such as, short circuits, over-voltage etc. In this research work, different electrical faults were also studied, taking cognizance of the causes and how they hinder power supply to various consumers in Abeokuta city. Important components such as the feeders, distributors and the aluminium conductors of the 33kv distribution network were assessed. The study was extended to the 33/11kv distribution system and effects of faults on this system were also statistically analyzed.